Digital Innovation in Radiology Education: Assessing the Impact of Instagram-Integrated Learning for Breast Ultrasound Skill. - Sebastián Rivadeneira Rojas; Vasileios Rafailidis; Florentina Guzmán-Aroca; Panos Prassopoulos (Revista Española de Educación Médica)
Over a 10-week period, 38 third-year medical students participated in an online course integrated into a basic breast ultrasound workshop. The primary objective of this article is to comprehensively assess the impact of the online self-directed training phase. In the experimental group, students engaged with a curated selection of publicly available audiovisual resources sourced from Instagram®, while the control group followed traditional instruction through conventional masterclasses using PowerPoint presentations. The experimental hypothesis posited that foundational breast ultrasound skills could be effectively acquired through the exploration of public Instagram content combined with self-assessment via Kahoot®. In this context, Kahoot® served not only as the platform for disseminating Instagram-related topics and links but also as a tool for ongoing formative assessments within the experimental group. A quasi-experimental design was employed, incorporating pre- and post-assessments and a control group for comparison. The findings demonstrated significant gains in both knowledge and confidence among students exposed to the gamified, Instagram-based intervention. Specifically, in the domain of Histology and Anatomy, the experimental group improved their post-test scores from 6.68 to 8.68, whereas the control group’s scores increased from 4.47 to 5.14. Regarding ultrasound physics knowledge, the experimental group's scores rose from 6.26 to 7.74, in contrast to an increase from 4.17 to 4.90 in the control group. In terms of understanding normal breast anatomy, the experimental group achieved a post-test score of 6.83, while the control group improved from 4.79 to 6.79. Moreover, the experimental group demonstrated a marked improvement in their ability to identify benign and suspicious breast findings. Self-assessment data indicated enhanced confidence in ultrasound skills among experimental group participants, who also reported high levels of enthusiasm for the program, reflected in an average satisfaction rating of 4.63 out of 5. This elevated satisfaction may contribute to increased program visibility and future enrollment. Despite these encouraging results, the limited sample size (19 participants per group) restricts the generalizability of the findings. Future research should involve larger sample sizes and longitudinal designs to better evaluate knowledge retention and the long-term impact of social media platforms on medical education.